Casos y cosas: semanario popular (Vol. 2, No. 67) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Desde mi tribuna, Arrojado a la charca, Lección de francés, El sueño de un marido, Buzón, Correo franco y con franqueza, Pica-pica.

ENGLISH: Includes: From my rostrum, Thrown into the pond, French lesson, A husband's dream, Letterbox, Franco mail and with frankness, Pica-pica
Cases and things: popular weekly magazine (Vol. 2, No. 67)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas